Investigating IL-22 gene polymorphism in patients afflicted with inflammatory bowel disease - Ali Moravej; Manouchehr Rasouli; Amin Fathpour; Abbas Mirshafiey; Seyed Alireza Razavi; Seyyede Ozra Shamsdin (Fasa University of Medical Sciences, 2017)
Background & Objective: inflammatory bowel disease is related to a group of chronic inflammatory disorders with unknown etiology which involves the digestive system. This disorder is divided into two major conditions including ulcerative colitis and crohn's disease. Recent studies show that interleukine-22, a member of IL-10 cytokine family, has influence on inflammatory processes during the disease. The purpose of this study was to investigate the relationship between IL-22 gene polymorphism (rs2227503) and the susceptibility to inflammatory bowel disease. Materials & Methods: 89 patients and 201 healthy individuals who referred to the Namazi Hospital of Shiraz, Iran, participated in this case-control study. Blood samples were collected and their genomic DNA were extracted. Restriction fragment length polymorphisms-Polymerase chain reaction technique was performed. Data were analyzed using a Chi-square test.  Results: The frequencies of allele and genotypes in patients and control group were calculated. Although the frequency of G allele was greater in patients and A allele was lower in patients compared with control group, the difference was not statistically significant. Conclusions:  There is no statistically significant relationship between IL-22 gene polymorphism (rs2227503) and the susceptibility to inflammatory bowel disease. More studies are required to clarify the exact role of IL-22 in pathogenesis of inflammatory bowel disease.